2011
DOI: 10.2147/dnnd.s16374
|View full text |Cite
|
Sign up to set email alerts
|

Profile of oral laquinimod and its potential in the treatment of multiple sclerosis

Abstract: Abstract:The medications available to treat relapsing-remitting multiple sclerosis (RRMS) are expanding as newer, and more potent, disease-modifying treatments become available. In particular, there is an impetus for safe and effective oral options. Laquinimod is a novel oral immunomodulator currently under investigation for the treatment of RRMS. Although the exact mechanism of action is not known, laquinimod is not an immunosuppressant. Rather, it appears to have multiple effects on the immune system, includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…An early study on laquinimod found that it could disrupt the ability of very late antigen-4 to bind with VCAM-1, thereby potentially mitigating the migratory capacity of T cells. 31 A more recent study found that laquinimod could reduce the adhesiveness of the central nervous system endothelium through reduced expression of cellular adhesion molecules. 32 Here, we found that laquinimod could indeed reduce the expression of VCAM-1 and E-selectin induced by TNF-α.…”
Section: Discussionmentioning
confidence: 99%
“…An early study on laquinimod found that it could disrupt the ability of very late antigen-4 to bind with VCAM-1, thereby potentially mitigating the migratory capacity of T cells. 31 A more recent study found that laquinimod could reduce the adhesiveness of the central nervous system endothelium through reduced expression of cellular adhesion molecules. 32 Here, we found that laquinimod could indeed reduce the expression of VCAM-1 and E-selectin induced by TNF-α.…”
Section: Discussionmentioning
confidence: 99%